Maize Endophytic Bacterial Diversity as Affected by Soil Cultivation History - Correa-Galeote, David; Bedmar, Eulogio J.; Arone, Gregorio J. (Frontiers in Microbiology, 2018)
The bacterial endophytic communities residing within roots of maize (Zea mays L.) plants grown in soils from the Quechua maize belt (Peruvian Andes) were examined using tags pyrosequencing spanning the V4 and V5 hypervariable regions of the 16S rRNA. Across four replicate libraries, two corresponding to sequences of endophytic bacteria from long time maize-cultivated soils and the other two obtained from fallow soils, 793 bacterial sequences were found that grouped into 188 bacterial operational taxonomic units (OTUs, 97% genetic similarity), of which 138 were present in the libraries from the maize-cultivated soils and 80 in the libraries from fallow soils. A mean of 30 genera were found in the fallow soil libraries and 47 were in those from the maize-cultivated soils. Both alpha and beta diversity indexes showed clear differences between bacterial endophytic populations from plants with different soil cultivation history. The number of sequences corresponding to main genera Sphingomonas, Herbaspirillum, Bradyrhizobium and Methylophilus in the maize-cultivated libraries were statistically more abundant than those from the fallow soils. Sequences of genera Dyella and Sreptococcus were significantly more abundant in the libraries from the fallow soils. Relative abundance of genera Burkholderia, candidatus Glomeribacter, Staphylococcus, Variovorax, Bacillus and Chitinophaga were similar among libraries. A canonical correspondence analysis of the relative abundance of the main genera showed that the four libraries distributed in two clearly separated groups. Our results suggest that cultivation history is an important driver of endophytic colonization of maize plants as the previous 5-year plant cultivation increased richness of their bacterial endophytes.